Ordered Semiconductor Photoanode Films for Dye-Sensitized Solar Cells Based on Zinc Oxide-Titanium Oxide Hybrid Nanostructures - Gao, Xiang-Dong; Wang, Cai-Lu; Gan, Xiao-Yan; Li, Xiao-Min (IntechOpen, 2011)
None